Nuclear power : A Boon or a Bane to The Society (Trinity Journal of Management, IT & Media (TJMITM), 2011)
certain elements that compose matter emit particles and  radiations spontaneousl Thisphenomenon ,s ref erred lo  as • radioactivity'. It cannot b altered by application_ of  heat. electncity or any other force and remams  unchangeable Three different 1-.mds of rays, known as  alpha, beta and gamma rays are associated with  radioactivity Toe alpha rays consist of particles (nuclei of  helium atoms) carrying a positive charge. The beta rays  particles have negative charge (stream of electrones).  The gamma rays are chargeless electromagnetic  radiation with shorter wavelengths than any X-rays.  Nuclear radiation arises from hundreds of different kinds  of unstable atom While many exist in nature the majority  are created m nuclear reaction. Nuclear fussion is the  process of splitting atoms, or fissioning them. Nuclear  fussion was discovered in 1938 after nearly five decades  of work by Ernest Rutherford, Henri Becquerel, Marie  Cruise and Pierre Cruise who elaborate that the nucleus  though tightly bond, could undergo different forms or  radioactive decay and could transmute into other  elements. It is nuclear fission that produces energy for  nuclear power Nuclear fission happens naturally every  day. Uranium, for example, constantly undergoes  spontaneou_s fission_ at a very slow rate. This is why the  element em~ radiation, and why ifs natural choice for the  induced fission that nuclear power plants require.
Keywords: radioactivity; Nuclear radiation; Nuclear fussion; nuclear power; Uranium